Le néré, un arbre du patrimoine de la Haute Guinée - Mabetty Touré (Belgeo)
The Néré (Parkia biglobosa), a naturally grown fruit-tree from the Guinean savannah and particularly from Upper Guinea, is well known in this region because of its great importance in nutrition and in traditional medicine, together with a well-marked patrimonial nature. From the néré fruit-tree viewed as an object of patrimony, this article attempts to indicate that women have accumulated over the years a know-how that was a pawn of the patrimonial nature of this product. However, the progressive monetization of the economy fuelled by the rise of the néré value in the market have been attracting more and more men into the business to the point of controlling the whole process. Consequently, the development of a market sector and the emergence of new players in a context of gender inequity are discussed as a threat to the patrimonial nature of the fruit-tree.